New Perspectives in Forest Science - Filipe dos Santos Viana, Helder; Antonio García Morote, Francisco (IntechOpen, 2018)
Forest management should allow the sustainable use of forests. This is only possible through solid knowledge in the disciplines that forest science encompasses. The readers of New Perspectives in Forest Science have an excellent source of information on actual trends of forest research and knowledge about the use of forest and landscape. This book has been written by specialists focusing on the following aspects of forest science: C cycle, biomass, forest restoration, forest resources and biodiversity. The authors of this book are of different nationalities and specialties, thus providing diverse perspectives on the subject of forestry. We hope that the chapters of this book can serve both students and researchers, as excellent guides to improve their knowledge on forest science.